Theory And Experiments Relating To Electromagnetic Fields Of Buried Sources With Consequences To Communication And Location - Richard G. Geyer (The National Institute for Occupational Safety and Health (NIOSH), 1973)
One aspect of a program to improve the chances of survival following coal mine disasters is the development of a communications system which will allow surviving miners to make their circumstances known to rescue teams. Various communications techniques can be considered, including electromagnetic systems, acoustic systems, and hybrid systems. The electromagnetic and acoustic systems would be independent of existing mine communications systems and set up specifically for use in emergencies. Hybrid systems might use a short emergency link to existing telephone systems in the mine. Many variations are technically possible, and the primary task is in evaluating the relative merits of each, so that the most workable system can be selected.